The effects of pre- and per-cooling interventions used in isolation and combination on subsequent 15-minute time-trial cycling performance in the heat - Moss J. N.; Trangmar, S. J.; Mackenzie, R. W. A.; Tyler, C. J. (Journal of Science and Medicine in Sport, 2021)
Objectives: To investigate the effects of pre- and per-cooling interventions on subsequent 15-min time-trial (TT) cycling performance in the heat. Design: Randomized cross-over design. Methods: Nine male athletes completed four experimental trials in the heat (40 °C, 50% rh): no-cooling (CON); warm-up per-cooling (PER: neck-cooling collar applied during the preload); pre-cooling (PRE: 30 min of cold water (22 °C) immersion [CWI]); and pre- and per-cooling combined (PRE + PER). In each trial, participants completed a 45-min preload exercise (50% V?O2peak), followed by a 15-min TT. Physiological (rectal [Tre], skin [Tsk], and neck [Tneck] temperature, and heart rate [HR]) and perceptual data (ratings of perceived exertion [RPE], thermal comfort [TC] and thermal sensation [TS]) were measured throughout. Results: Tre and Tsk were lower in PRE and PRE + PER at the start of the preload (p < 0.001). Tre remained lower throughout the preload following CWI although these differences were no longer present at the start of the TT (p = 0.22). Tneck was lowered throughout in PER and PRE + PER (p < 0.001). No other physiological or perceptual differences were observed at the start or end of the preload or TT. Participants covered a similar TT distance in all trials (15.7-15.9 km, p = 0.77). Conclusions: Pre-cooling induced thermoregulatory benefits for ~45 min and perceptual benefits for the same duration when supplemented with per-cooling. Neck per-cooling offered no such benefits when used in isolation. Neither pre- nor per-cooling, in isolation or combination, improved subsequent 15-min cycling time-trial performance in well-trained participants in the heat (40 °C).